The relative benefits and risks of stablecoins as a means of payment: A case study perspective - Annetta Ho; Sriram Darbha; Yuliya Gorelkina; Alejandro García (Bank of Canada, 2022)
Our paper contributes to the discussion about the utility of stablecoins for retail payments through an objective, evidence-based approach that compares stablecoins with traditional retail payment methods. The paper also provides insights that could be useful in the design of central bank digital currencies. We identify the potential benefits, risks and costs of stablecoin arrangements used for retail payments relative to traditional retail payment methods. We select three real-world examples for comparison: (i) a Mastercard credit card payment through a traditional bank; (ii) a Unified Payments Interface fast payment through Paytm (a technology-enabled payments company regulated as a limited-purpose bank); and (iii) a stablecoin retail transaction using USD Coin and a BitPay wallet. We find that certain stablecoin arrangements offer end users greater control of their privacy, facilitate more rapid innovation and have the potential to increase transaction speeds, particularly for cross-border payments. At the same time, stablecoins may provide less consumer protection for fraud, present higher risks to the payment system and to efforts to combat financial crime (partly because of the more nascent regulatory framework), and be costlier relative to traditional payment arrangements. Our findings suggest that stablecoin arrangements do not currently serve as substitutes for the suite of traditional payment arrangements but instead address niche use cases or user segments that value their benefits and can accept their risks or costs.
Keywords: D78; O38; 330; Digital currencies and fintech; Payment clearing and settlement systems